Allele Frequencies of 10 Autosomal STR Loci from Chakma and Tripura Tribal Populations in Bangladesh. (10th May 2010) - Ferdous, Ahmad; Ali, Mohammad Eunus; Alam, Shafiul; Hasan, Mahamud; Hossain, Tania; Akhteruzzaman, Sharif
Abstract : Allele frequencies of ten autosomal STR loci, D3S1358, vWA, D16S539, D2S1338, D8S1179, D21S11, D18S51, D19S433, TH01, and FGA were investigated in Chakma and Tripura tribal populations of Bangladesh. In both the populations, all loci were in Hardy-Weinberg equilibrium except for FGA locus in Chakma and D21S11 in Tripura. All the loci were highly polymorphic in Chakma population with an observed heterozygosity( H o ) of> 0.7 and moderately polymorphic in Tripura population( H o > 0.6 ) . However, both the population showed least polymorphism at TH01 locus( H o < 0.6 ) . A comparison between Chakma and Tripura population data revealed statistically significant differences in allele frequency distribution for most of the loci. A similar comparison with the mainstream Bengali population using previously published data from this lab also showed significant difference in allele frequency with these two tribal populations.